European Union and the deconstruction of the Rhineland frontier - Loriaux, Michael Maurice (Cambridge University Press, 2008)
The Rhineland region includes the core regional economy of western Europe, encompassing Belgium, Luxemburg and parts of the Netherlands, France, Switzerland and Germany. Throughout history there have been tensions between this region's roles as a frontier and as western Europe's economic core. Michael Loriaux argues that the European Union arose from efforts to deconstruct this frontier. He traces Rhineland geopolitics back to its first emergence, restoring frontier deconstruction to the forefront of discussion about the EU. He recounts how place names were manipulated to legitimate political power and shows how this manipulation generated the geopolitics that the EU now tries to undo. Loriaux also argues that the importance of this issue has significantly affected the nature of the EU's development and helps condition a festering legitimation crisis